Socialist law in Socialist East Asia - Fu, Hualing; Gillespie, John, (John Stanley); Nicholson, Penelope; Partlett, William, 1979- (Cambridge, United Kingdom : Cambridge University Press, 2018)
A unique comparison of laws and institutional designs in two continuing socialist states: China and Vietnam. The book will appeal to scholars and graduate students researching comparative law, socio-legal studies, Asian laws, Chinese law, Vietnamese law, and law and development.
What is not socialist about Socialist law / Michael Dowdle -- The historical roots of Socialist law / William Partlett -- Socialist rule of law with Chinese characteristics : a new genealogy / Glenn Tiffert -- The Soviet legacy and its impact on contemporary Vietnam / Pham Duy Nhia -- Diverging trends in the Socialist constitutionalism of the People's Republic of China and the Socialist Republic of Vietnam / Hualing Fu and Jason Buhi -- Constitutional dualism : socialism and constitutionalism in contemporary Vietnam / Bui Ngoc Son -- Democratic centralism and administration in China / Sarah Biddulph -- Roots and routes : adapting the Soviet-inspired Vietnamese court and procuracy system / Pip Nicholson and Pham Lan Phuong -- What is socialist about labour law in China? / Aaron Halegua and Cynthia Estlund -- Strike settlement in transitional Vietnam and the persistence of Socialist and Marxist-Leninist influences / Do Hai Ha -- Is Vietnam transitioning out of socialism or transforming socialism? searching for answers in commercial regulation / John Gillespie -- The influence of socialist principles on the legal regulation of markets in China / Wendy Ng -- The evolution of the property system in China : between the Socialist heritage and liberal market / Wendy Ng -- From revolution to evolution : the changing meanings of Socialist land in Vietnam / John Gillespie and Toan Le
Includes bibliographical references and index.
Keywords: Law and socialism; Rule of law -- China; Socialism -- China; Socialism -- Vietnam; Law reform -- China; Law reform -- Vietnam; Socialism -- East Asia